2007
DOI: 10.1017/s0029665107005344
|View full text |Cite
|
Sign up to set email alerts
|

Cues to overeat: psychological factors influencing overconsumption

Abstract: Human food intake is driven by necessity, but modern industrialized societies are characterized by food surfeit and an increasingly 'obesogenic' environment. This environment tends to discourage energy expenditure and to facilitate energy intake. The amount eaten in any given eating episode depends less on internal need state and more on environmental contextual factors such as the availability of highly-palatable energy-dense foods. In addition, the process of satiation can easily be disrupted by the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 91 publications
(142 reference statements)
0
48
0
1
Order By: Relevance
“…Following Edmund Rolls' discovery of sensory-specific satiety revealed by the selective reduction in the responses of lateral hypothalamic neurons to a food eaten to satiety (3,5) , it has been shown that this is implemented in a region that projects to the hypothalamus, the orbitofrontal (secondary taste) cortex, for the taste, odour and sight of food (4,34) . This evidence shows that the reduced acceptance of food that occurs when food is eaten to satiety, the reduction in the pleasantness of its taste and flavour, and the effects of variety to increase food intake (6)(7)(8)(35)(36)(37)(38)(39)(40)(41)(42)(43) are produced in the OFC, but not at earlier stages of processing where the responses reflect factors such as the intensity of the taste, which is little affected by satiety (32,44) . In addition to providing an implementation of sensory-specific satiety (probably by habituation of the synaptic afferents to orbitofrontal neurons with a time course of the order of the length of a course of a meal), it is likely that visceral and other satiety-related signals reach the OFC (as indicated in Fig.…”
Section: The Secondary Taste Cortexmentioning
confidence: 97%
“…Following Edmund Rolls' discovery of sensory-specific satiety revealed by the selective reduction in the responses of lateral hypothalamic neurons to a food eaten to satiety (3,5) , it has been shown that this is implemented in a region that projects to the hypothalamus, the orbitofrontal (secondary taste) cortex, for the taste, odour and sight of food (4,34) . This evidence shows that the reduced acceptance of food that occurs when food is eaten to satiety, the reduction in the pleasantness of its taste and flavour, and the effects of variety to increase food intake (6)(7)(8)(35)(36)(37)(38)(39)(40)(41)(42)(43) are produced in the OFC, but not at earlier stages of processing where the responses reflect factors such as the intensity of the taste, which is little affected by satiety (32,44) . In addition to providing an implementation of sensory-specific satiety (probably by habituation of the synaptic afferents to orbitofrontal neurons with a time course of the order of the length of a course of a meal), it is likely that visceral and other satiety-related signals reach the OFC (as indicated in Fig.…”
Section: The Secondary Taste Cortexmentioning
confidence: 97%
“…9,10 Eating behavior in humans is an extremely complex process modulated by internal homeostatic processes [11][12][13] and environmental and social influences. 14,15 As such, energy homeostasis aims to match energy intake with overall energy needs; however, total food intake is also influenced by external factors, such as food availability and palatability, which might lead to excess energy intake during any given meal. 16 This tendency to eat beyond immediate homeostatic needs has presumably evolved because the motivation to seek and consume calories contributed to survival when food sources were scarce and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Following Edmund Rolls' discovery of sensory-specific satiety revealed by the selective reduction in the responses of lateral hypothalamic neurons to a food eaten to satiety, 24,25 it has been shown that this is implemented in a region that projects to the hypothalamus, the orbitofrontal (secondary taste) cortex, for the taste, odour and sight of food. 26,27 This evidence shows that the reduced acceptance of food that occurs when food is eaten to satiety, the reduction in the pleasantness of its taste and flavour, and the effects of variety to increase food intake, [28][29][30][31][32][33][34][35][36][37][38][39] are produced in the OFC, but not at earlier stages of processing in which the responses reflect factors such as the intensity of the taste, which is little affected by satiety. 22,40 In addition to providing an implementation of sensory-specific satiety (probably by habituation of the synaptic afferents to orbitofrontal neurons with a time course of the order of the length of a course of a meal), Figure 1 Schematic diagram showing some of the gustatory, olfactory, visual and somatosensory pathways to the OFC, and some of the outputs of the OFC, in primates.…”
Section: Introductionmentioning
confidence: 99%